2018
DOI: 10.1002/admi.201800082
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Wire‐Shaped Perovskite Photodetector via Joule Heating for Improved Crystallization and Performance

Abstract: UV region with the best results showing 0.9 A W −1 responsivity and 0.28/5.3 s rise/decay time. When following a vertical device structure with multiple layers this complexity adds to both fabrication cost and difficulty. [5a,6] We herein report the development of a carbon-based flexible wire-shaped perovskite photodetector. This flexible wire-shaped device performs exceedingly well under low light environments (11 A W −1 ) and is easily woven into composites due to its flexibility and small diameter (≈400 µm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 57 publications
(48 reference statements)
0
17
0
Order By: Relevance
“…Comparing with recently reported flexible perovskite photodetectors working in the visible range (summarized in Table ), our flexible photodetector exhibits several characteristics: (i) Ultrathin active layer with 20 nm in thickness, which is the thinnest flexible perovskite photodetector to the best of our knowledge. (ii) High responsivity up to 5600 A/W, much higher than that of previously reported flexible perovskite photodetectors for 2 orders of magnitude, which demonstrates the remarkable detection efficiency of the photodetector. (iii) Fast response with the rise/fall time of 3.2/9.2 μs, which gives rise to an outstanding 3 dB bandwidth up to 0.2 MHz.…”
Section: Introductionmentioning
confidence: 84%
“…Comparing with recently reported flexible perovskite photodetectors working in the visible range (summarized in Table ), our flexible photodetector exhibits several characteristics: (i) Ultrathin active layer with 20 nm in thickness, which is the thinnest flexible perovskite photodetector to the best of our knowledge. (ii) High responsivity up to 5600 A/W, much higher than that of previously reported flexible perovskite photodetectors for 2 orders of magnitude, which demonstrates the remarkable detection efficiency of the photodetector. (iii) Fast response with the rise/fall time of 3.2/9.2 μs, which gives rise to an outstanding 3 dB bandwidth up to 0.2 MHz.…”
Section: Introductionmentioning
confidence: 84%
“…Regarding other aggregates, Adams et al recently reported CNT yarns with organolead triiodide perovskite wrapped as wire-shaped heterostructures, which can be used as self-powering photodetectors with high performance. 69 Wang and Kumta reported the synthesis of heterostructures consisting of CNT vertical arrays and nanoscale amorphous/nanocrystalline Si droplets using a simple two-step liquid-injection CVD process, which has potential for use in high-capacity Li-ion anodes. 70 Therefore, according to the special band structures of CNTs, proper band engineering based on the target device is necessary.…”
Section: Construction Of Heterostructuresmentioning
confidence: 99%
“…Thin film PDs play important roles in video imaging, optical communication, and environmental monitoring. [1][2][3][4][5][6][7][8] Antimony sulfide (Sb 2 S 3 ), a binary compound, has a single phase, a large content, and is non-toxic. The suitable bandgap of 1.73 eV and the absorption coefficient greater than 10 5 cm −1 in the visible light range make In this work, we design a depleted Sb 2 S 3 thin film photoconductive detector with the structure of Au/(glass/TiO 2 :) Sb 2 S 3 /Au by introducing a TiO 2 layer between the Sb 2 S 3 film and the glass substrate.…”
Section: Introductionmentioning
confidence: 99%